Accentuation and Attention: From Perceptual Organization to Consciousness - Baingio Pinna; Daniele Porcheddu; Jurģis Šķilters (Brain Sciences)
Background: This study investigates the complex relationship between accentuation and attention in visual perception, extending classical Gestalt principles by introducing dissimilarity as a complementary mechanism to similarity in perceptual organization. Objectives and Methods: Through a series of phenomenological experiments, we demonstrate how accentuation, driven by dissimilarity, plays a crucial role in shaping visual experience and guiding attention. Results: Our findings reveal that accentuation serves as a pre-attentive mechanism for highlighting salient features, influencing initial perceptual organization, and modulating the apparent shape and orientation of visual elements. We show that while accentuation operates rapidly and automatically, attention acts as a flexible, selective mechanism that can either reinforce or override accentuation-based percepts. This interplay suggests a two-stage process of visual perception, with implications for theories of consciousness and information processing in biological systems. This study also explores the evolutionary significance of accentuation in camouflage and sexual selection, providing insights into how perceptual mechanisms may have evolved to enhance adaptive fitness. Conclusions: Our results have broad implications for understanding visual cognition, design, and clinical applications related to attentional disorders.